2012
DOI: 10.1016/j.celrep.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding by GATA Transcription Factor Suggests Mechanisms of DNA Looping and Long-Range Gene Regulation

Abstract: Summary GATA transcription factors regulate transcription during development and differentiation by recognizing distinct GATA sites with a tandem of two conserved zinc fingers and by mediating long-range DNA looping. However, the molecular basis of these processes is not well understood yet. Here, we determined three crystal structures of the full DNA binding domain (DBD) of human GATA3 protein, which contains both zinc fingers, in complex with different DNA sites. In one structure, both zinc fingers wrap arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 55 publications
4
105
0
Order By: Relevance
“…The N and C fingers in a single GATA1 molecule individually bind to two GATA motifs aligned in a palindromic orientation, indicating that the N finger contributes to the specific bivalent binding of GATA1 to Pal-GATA. In this regard, structural analysis of GATA3 revealed that N finger binds the opposite face of DNA that is bound by C finger and the N finger interacts with the C-terminal basic tail of the C finger inserted into the minor groove (39). This model nicely supports the notion that N finger does not contribute to GATA1 binding to rPal-GATA, in which two GATA motifs are aligned in a reverse palindromic orientation.…”
Section: Discussionsupporting
confidence: 63%
“…The N and C fingers in a single GATA1 molecule individually bind to two GATA motifs aligned in a palindromic orientation, indicating that the N finger contributes to the specific bivalent binding of GATA1 to Pal-GATA. In this regard, structural analysis of GATA3 revealed that N finger binds the opposite face of DNA that is bound by C finger and the N finger interacts with the C-terminal basic tail of the C finger inserted into the minor groove (39). This model nicely supports the notion that N finger does not contribute to GATA1 binding to rPal-GATA, in which two GATA motifs are aligned in a reverse palindromic orientation.…”
Section: Discussionsupporting
confidence: 63%
“…As these elements are located distant from each other in the comt promoter (30 bp apart), this cooperative binding of the heterodimer would likely involve a DNA loop comprising three helical turns of the DNA (Figure 8). Such a mechanism was classically proposed in the lambda bacteriophage (Hochschild and Ptashne, 1986) and in humans (Chen et al, 2012;Sanyal et al, 2012). In the case of plants, cooperative binding via DNA-looping of heteromeric transcription factors has been demonstrated in the case of MADS box proteins.…”
Section: Discussionmentioning
confidence: 98%
“…However, the zinc finger domains of GATA1-3 are highly conserved, with all mutated residues being identical (Supplemental Figure 5). A homology model of the GATA2 C-terminal zinc finger (Supplemental Figure 5), based on GATA3 bound to DNA (52) indicates that the Emberger R361L and R396Q mutations likely disrupt binding to DNA by mutation of key residues that interact with the major and minor grooves, respectively ( Figure 2D). R362 makes some minor interactions with phosphates on the backbone ure 2A).…”
Section: Gata2 Binds To and Transactivates Prox1 Regulatory Elementsmentioning
confidence: 99%